Regulating Cross-Border Transfer Pricing in a Changing Global Environment - Paul, Jennifer (Université d'Ottawa | University of Ottawa, 2012)
This paper provides a review of the literature on transfer pricing from the perspective of the regulator. A short description of the regularory challenges posed by the vertically integrated firm and the multinational enterprise is presented, followed by l